From knowledge to decision: A PLS-MGA investigation of halal fashion purchase behaviour across generation in Indonesia - Z Zahro; Ahmad Syaiful Affa; Kamalina Din Jannah; Muhammad Shofiyuddin; Zahri Irawan; Laela Nur Fahmi (Diponegoro International Journal of Business, 2025)
Halal fashion consumption in Indonesia is rapidly evolving at the intersection of religious identity, modern lifestyle, and ethical consumerism. However, prior research has largely emphasized religiosity, with limited attention to cognitive and lifestyle dimensions across generational cohorts. This study examines the structural relationships between consumer knowledge, halal awareness, lifestyle orientation, and halal fashion purchase decisions, while exploring generational differences among Muslim consumers using Partial Least Squares Multi-Group Analysis (PLS-MGA). A cross-sectional survey of 504 Muslim respondents from Generations X, Y, and Z was analyzed using WarpPLS 8.0. Results indicate that consumer knowledge strongly influences both halal awareness and lifestyle, but has a weak direct effect on purchase decisions. Lifestyle emerges as the strongest predictor of halal fashion consumption. PLS-MGA reveals significant generational differences, particularly in the effects of knowledge on lifestyle and awareness on purchase decisions, with Gen Z showing the strongest behavioral alignment. These findings highlight the need for generation-specific marketing: Gen Z responds to lifestyle and ethical identity, Gen Y to value integration between modernity and tradition, and Gen X to certification and institutional cues. This study advances halal consumer behavior theory by integrating lifestyle as a core construct and validating generational variations in a Muslim-majority context.